"Am I not human?": Reasserting humanness in response to group-based dehumanization. (December 2022) - Howe, Lauren C.; Schumann, Karina; Walton, Gregory M.
Research on group dehumanization has focused largely on the perpetrators of dehumanization or on its negative emotional and cognitive effects on targets. We theorized that people would also reassert their humanness in response to dehumanizing portrayals of their group. Experiment 1 showed that Black individuals responded to a dehumanizing representation of their racial group by emphasizing their experience of more complex, uniquely human emotions versus emotions more associated with other animals. Experiment 2 and a supplemental experiment showed that Black, but not White, individuals responded to group-based dehumanization by depicting more complex self-portrayals. Taken together, these studies begin to illustrate that targets of group-based dehumanization are not simply passive victims but respond actively, resisting negative representations of their group by reasserting their humanness.